Enantioselective Organocatalyzed Desymmetrization of 3-Substituted Cyclobutanones through Michael Addition to Nitroalkenes - Capitta, Francesca; Frongia, Angelo; Ollivier, Jean; Aitken, David J.; Secci, Francesco; Piras, Pier Paolo; Guillot, Régis (Synlett, 2015)
A new procedure for the desymmetrization of prochiral 3-substituted cyclobutanones has been established through organocatalyzed Michael addition to nitroalkenes. The approach provides enantiomerically enriched 2-alkyl-3-aryl(alkyl) cyclobutanones with three contiguous stereogenic centers. The optimum conditions were determined by screening of catalyst and reaction conditions and a transition-state model is proposed to account for the observed diastereomeric and enantiomeric selectivities.
Keywords: cyclobutanones; Michael addition; nitroalkenes; organocatalysis; stereoselectivity